Feeding Ecology of Gould's Arrow Squid "Nototodarus gouldi" (Cephalopoda: Ommastrephidae) in Aotearoa New Zealand Waters - Hu, Lucia; Bolstad, Kathrin; Stevens, Darren; Bennett, Jerusha; Braid, Heather (Wiley, 2026)
Squids are important components of marine ecosystems because of their role as both predator and prey. Across the Tasman Sea, Gould's arrow squid (Nototodarus gouldi) is a commercially targeted ommastrephid squid that supports an economically important fishery. However, the ecology of this species in Aotearoa New Zealand (NZ) waters remains poorly understood. This study is the first integrative analysis of the feeding ecology of N. gouldi within the NZ Exclusive Economic Zone. We analyzed gut contents by combining morphological observations to identify hard parts, DNA barcoding to identify soft tissue, and a parasite analysis to further understand trophic linkages and parasite-host associations. In total, 29 prey taxa spanning six phyla were identified, including 17 prey species not previously reported in the diet of N. gouldi. The most frequently occurring prey items include cephalopods (with evidence of cannibalism), crab megalopa, red rock crab, and opalfish. Two parasites were identified, which can be associated with anisakiasis in humans. Most individuals (68.8%) had Anisakis sp. larvae encysted in the wall of their stomach caecum, and three individuals had Hysterothylacium sp. within their gut contents. Our results suggest that N. gouldi has a diverse and opportunistic feeding strategy and plays an important role in coupling pelagic and benthic food webs. This ecological information is important for the development of ecosystem-based fisheries management models.
Keywords: 31 Biological Sciences; 3103 Ecology; 0608 Zoology; Ecology; 3109 Zoology; cephalopod; COI; dietary analysis; food spectrum; helminths; stomach caecum